The Austria-Hungarian Ultimatum to Serbia of October 1913 - Kocaqi, Elena (Mediterranean Journal of Social Sciences, 2012)
The Austria-Hungarian sent an ultimatum to Serbia in October 1913. This ultimatum is the first that was send to Serbia. Thesecond was sent in July of 1914 that was the principal pretext of First World War. The ultimatum was sent to oblige Serbia to withdrawfrom Albanian territories that were decided in the Conference of Ambassadors in London that year. Serbia asked from the great powersto undertake a modification of the decision that were taken to make able to change the borders in its favour and in contrary with GreatPowers decisions kept his army in Albanian state. This was not accepted by Austria-Hungarian that was the main power that contributedin the foundation of Albanian state. Serbia was decided to do not withdraw and to ignore the decision of Great Powers and Austria-Hungarian was decided to oblige it to withdraw with all the means. The conflict had all the components of a European war. For this paperI have made mostly researches in the Austria-Hungarian archives.